Adaptations, life-history traits and ecological mechanisms of parasites to survive extremes and environmental unpredictability in the face of climate change - Aleuy, O. Alejandro (Int J Parasitol Parasites Wildl, 2020)
Climate change is increasing weather unpredictability, causing more intense, frequent and longer extreme events including droughts, precipitation, and both heat and cold waves. The performance of parasites, and host-parasite interactions, under these unpredictable conditions, are directly influenced by the ability of parasites to cope with extremes and their capacity to adapt to the new conditions. Here, we review some of the structural, behavioural, life history and ecological characteristics of parasitic nematodes that allow them to persist and adapt to extreme and changing environmental conditions. We focus primarily, but not exclusively, on parasitic nematodes in the Arctic, where temperature extremes are pronounced, climate change is happening most rapidly, and changes in host-parasite interactions are already documented. We discuss how life-history traits, phenotypic plasticity, local adaptation and evolutionary history can influence the short and long term response of parasites to new conditions. A detailed understanding of the complex ecological processes involved in the survival of parasites in extreme and changing conditions is a fundamental step to anticipate the impact of climate change in parasite dynamics.